Comparative study of the biopharmaceutical quality of Diazepam 10 mg commercialized in the Peruvian market - Saavedra Suárez, Segundo Francisco; Curo Vallejos, Yuri; Gutierrez Ramos, Miriam; Alva Plasencia, Pedro; Rodriguez Saavedra, Lennin (Ars Pharmaceutica (Internet), 2021)
Introduction: diazepam belongs to a group of medicines called benzodiazepines. These drugs are known to work in the brain through GABA and, it used to relieve anxiety and control the agitation caused by alcohol withdrawal. Method: variation in weight, friability, hardness, disintegration time, quantification of active ingredient, speed and dissolution profile between the innovative and multi-source drugs marketed in the Peruvian market. The evaluation of these presentations did with the USP 42 Pharmacopeia. Results: the results established that all Diazepam 10 mg multi-source tablets included in this research are bioequivalent with the chosen innovative brand and, therefore, can be interchangeable. Conclusions: The results observed that the multi-source tablets of Diazepam 10 mg included in this research are bioequivalent with the innovator and, therefore, allow the determination of pharmaceutical equivalence as a support element in the decision-making process for purchasing in the service pharmacist.